Analisis SWOT sebagai Strategi dalam Peningkatan Kinerja Pegawai Pemerintahan - Yunas, Ibnu Prama; Sari , Juli Arsismen; Irvandhel, Muhammad; Syafwandi, Syafwandi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to formulate strategies that must be implemented for performance development by analyzing the company's strengths, weaknesses, opportunities, and threats through analysis on the Government. This research is qualitative descriptive research with a SWOT analysis method that aims to improve the performance of Government employees. Data collection is carried out through observation, interviews, and documentation. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. Based on the results and discussions that have been carried out previously, the author concludes that: the strategy used to improve employee performance is the SO (Strengths–Opportunities) strategy, actions that can be taken in the strengths strategy by increasing competence, extensive work experience and high competence. Meanwhile, the opportunities strategy is with the development of new technology that can improve work efficiency and reduce costs, the availability of quality human resources that can strengthen the work team.